Effectiveness of Cardiovascular Health Issue-Based Problem-Based Learning on Students’ Critical Thinking Skills - Billik, Agsen Hosanti Susana; Son, Rosalina; Putu Arnyana, Ida Bagus (Biosfer: Jurnal Tadris Biologi, 2026)
This research investigated the effect of Problem-Based Learning (PBL) integrated with cardiovascular health issues on students’ critical thinking skills in the circulatory system topic. A quasi-experimental design with a nonequivalent control group was applied. The participants were two eleventh-grade science classes, with 32 students in each class. The experimental class learned through cardiovascular issue-oriented PBL, whereas the control class was taught using conventional learning. Data were collected using an essay-based critical thinking test developed according to Facione’s indicators, including interpretation, analysis, evaluation, inference, explanation, and self-regulation. The data were examined using N-Gain analysis and an Independent Samples t-test. The findings revealed that students in the experimental class showed greater improvement than those in the control class. The experimental class obtained an N-Gain score of 63.87%, while the control class achieved 35.10%, both categorized as moderate. The statistical test produced a significance value of 0.000, which was below 0.05, indicating a significant difference between the two classes. Among the six indicators, evaluation and analysis showed the highest development. These results indicate that PBL integrated with cardiovascular health issues can be an effective instructional approach for strengthening students’ critical thinking skills in biology learning. Efektivitas Model Problem-Based Learning Berbasis Isu Kesehatan Kardiovaskular terhadap Kemampuan Berpikir Kritis Siswa ABSTRAK: Penelitian ini mengkaji pengaruh penerapan Problem-Based Learning (PBL) yang diintegrasikan dengan isu kesehatan kardiovaskular terhadap kemampuan berpikir kritis siswa pada materi sistem peredaran darah. Penelitian menggunakan desain kuasi eksperimen dengan bentuk nonequivalent control group. Subjek penelitian terdiri atas dua kelas XI IPA, masing-masing berjumlah 32 siswa. Kelas eksperimen mengikuti pembelajaran PBL berorientasi isu kesehatan kardiovaskular, sedangkan kelas kontrol mengikuti pembelajaran konvensional. Data dikumpulkan melalui tes uraian kemampuan berpikir kritis yang dikembangkan berdasarkan indikator Facione, meliputi interpretasi, analisis, evaluasi, inferensi, eksplanasi, dan regulasi diri. Analisis data dilakukan menggunakan N-Gain dan uji Independent Samples t-test. Hasil penelitian menunjukkan bahwa peningkatan kemampuan berpikir kritis siswa pada kelas eksperimen lebih tinggi dibandingkan kelas kontrol. Kelas eksperimen memperoleh nilai N-Gain sebesar 63,87%, sedangkan kelas kontrol memperoleh nilai 35,10%, dan keduanya berada pada kategori sedang. Hasil uji statistik menunjukkan nilai signifikansi sebesar 0,000, lebih kecil dari 0,05, sehingga terdapat perbedaan yang signifikan antara kedua kelas. Indikator yang mengalami perkembangan paling tinggi adalah evaluasi dan analisis. Dengan demikian, PBL yang diintegrasikan dengan isu kesehatan kardiovaskular dapat menjadi pendekatan pembelajaran yang efektif untuk memperkuat kemampuan berpikir kritis siswa dalam pembelajaran biologi.